(untitled) (Journal of Asian Development Studies, 2023)
The focus of this study is on the risk factors for fixed partial denture (FPD) failure in patients at (BKCD) Mardan for improving clinical results and patient satisfaction. Failure of the FPD can result in various issues affecting oral function and aesthetics. Investigating these risk factors helps improve treatment protocols and resource allocation in prosthodontic practice and promotes a preventative dentistry approach. The study’s location at (BKCD) Mardan provides local relevance and may provide insights particular to the regional population, adding vital knowledge to the larger field of dentistry research. With an enormous sample of 134 participants, gender distribution in our research study showed a somewhat balanced representation, with 65 people (48.5%) presenting as male and 69 (51.5%) responding as female. The bulk of participants, 64.9% of the total, are between the ages of 15 and 45, and in contrast, 35.1% of our participants are between the ages of 46 and 60. Our study looked at two essential factors: wear duration and failure duration. Regarding wear length, 39.6% of participants said they had worn their FPDs for less than a year. Furthermore, 30.6% of participants said they had used their FPDs for 1 to 6 years. 29.9% of participants had worn their FPDs for more than six years and the length of failure. FPD failures were reported by 38.1% of participants within the first six months of usage. A further 19.4% of patients failed between 7 and 12 months. Surprisingly, 42.5% of patients experienced failures after more than a year of FPD usage. Regarding oral hygiene, 38.1% of participants reported good oral hygiene practices, whereas 61.9% reported poor oral hygiene habits. In conclusion, this study has shed light on the risk variables related to fixed partial denture (FPD) failure among patients